2022
DOI: 10.1016/j.breast.2022.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory analysis of biomarkers associated with clinical outcomes from the study of palbociclib plus endocrine therapy in premenopausal women with hormone receptor-positive, HER2-negative metastatic breast cancer

Abstract: Background: Palbociclib plus endocrine therapy (ET) demonstrated significant progression-free survival (PFS) benefit in Young Pearl, a randomized phase ll trial comparing palbociclib þ ET versus capecitabine in premenopausal women with hormone receptor positive, HER2 negative metastatic breast cancer (MBC). This exploratory analysis investigated potential biomarkers of palbociclib plus ET on PFS. Patients and methods: Of 178 patients randomized (92 palbociclib plus ET; 86 capecitabine), we performed targeted s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…Additionally, compared with patients of EUR ancestry, patients of EAS ancestry with HER2+ BC and TNBC, as well as patients of SAS ancestry with HER2+ BC, were more likely to have tumors that harbor PIK3CAmut (Figs 2A, 2C and 2E). The ancestry-specific tumor PIK3CAmut prevalences observed across BC subtypes is supported by the findings from studies that sampled substantially fewer participants in Africa, [36][37][38][39] Latin America, [40][41][42][43][44] China or Korea, [45][46][47][48][49][50][51][52] and South Asian countries. [53][54][55][56][57] Inconsistencies between PIK3CAmut prevalences identified in our study and those reported in the literature were observed when sample sizes were small and when differences existed in the clinical characteristics of the populations evaluated and/or assay methodologies.…”
Section: Discussionmentioning
confidence: 72%
“…Additionally, compared with patients of EUR ancestry, patients of EAS ancestry with HER2+ BC and TNBC, as well as patients of SAS ancestry with HER2+ BC, were more likely to have tumors that harbor PIK3CAmut (Figs 2A, 2C and 2E). The ancestry-specific tumor PIK3CAmut prevalences observed across BC subtypes is supported by the findings from studies that sampled substantially fewer participants in Africa, [36][37][38][39] Latin America, [40][41][42][43][44] China or Korea, [45][46][47][48][49][50][51][52] and South Asian countries. [53][54][55][56][57] Inconsistencies between PIK3CAmut prevalences identified in our study and those reported in the literature were observed when sample sizes were small and when differences existed in the clinical characteristics of the populations evaluated and/or assay methodologies.…”
Section: Discussionmentioning
confidence: 72%
“…However, the authors pointed out that the analysis was only exploratory and other studies would be necessary to acquire more consistent data [17]. In a recent analysis of the YOUNG PEARL trial [30], which compared the efficacy of palbociclib + exemestane + LHRH analogue vs. capecitabine in pre-menopausal women with HR+/HER2-mBC not previously treated with aromatase inhibitors, Lee et al confirmed better PFS in luminal vs. non-luminal subtypes in pts receiving combined treatment, excluding those with a pathogenetic BRCA2 mutation, characterized by worse prognosis regardless of subtype. However, this finding was not confirmed by the analysis of pts treated in MONALEESA trials [23], in which the addition of ribociclib resulted in an increase in PFS in all subtypes excluding basal-like, and furthermore, HER2E appeared to be the subtype that benefited most from the addition of ribociclib, although it is known to have a worse prognosis and show greater endocrine resistance than the luminal subtypes [7,8] (differences in PFS between experimental and control groups divided by intrinsic subtype were as follows: HER2E 10.8 months, LumA 10.1 months, LumB 9.4 months, basal-like 0.2 months, normal-like 11.24 months).…”
Section: Discussionmentioning
confidence: 99%
“…The genes FGFR2 , CCND1 and TOX3 are still not studied much in relation to the roles in breast cancer although genetic studies have suggested their involvement in cancer risk. FGFR2 has been suggested to be implicated in breast cancer as a target for therapeutic strategies [ 44 ], CCND1 is frequently mutated by copy number variation and suggested as a prognostic biomarker [ 45 ]. The role of TOX3 in relation to breast cancer is less clear.…”
Section: Discussionmentioning
confidence: 99%